Oculo-dento-digital dysplasia: a systematic analysis of published dental literature - Karshma Devi Hindu; Fahad Umer (Nature Publishing Group, 2023)
Abstract Introduction Oculo-dento-digital dysplasia (ODDD, OMIM# 164200) is a rare genetic disorder caused by mutation in Gap junction alpha gene that encodes connexin 43 (Cx43) protein. In this paper, the case of a 16-year-old boy is reported who presented with the complaint of toothache. Examination revealed unusual facial features, i.e., long narrow nose, hypertelorism, prominent epicanthal folds along with syndactyly and camptodactyly. We have also compiled available dental literature on ODDD that will help clinicians in early diagnosis and management of this condition. Materials and methods A literature search was performed in PubMed NLM, EBSCO Dentistry & Oral Sciences Source, and EBSCO CINAHL Plus. Results A total of 309 articles were identified in the literature search. Only 17 articles were included based on the predetermined inclusion and exclusion criteria in the review synthesis. The included articles were case reports (n = 15), a case report and review (n = 1), and an original article (n = 1). Enamel hypoplasia, hypomineralization, microdontia, pulp stones, curved roots, and taurodontism were common dental findings in ODDD. Conclusions After establishing definitive diagnosis, a multidisciplinary team should work in cohesion to improve the quality of life of patients. Immediate treatment should be focused on the correction of current oral condition and symptomatic treatment. In the long term, attention should be diverted to prevent tooth wear and maintaining the occlusal vertical dimension to establish adequate function.